(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
This study aims to compare two methodologies routinely used for lipoaspiration- a standard Suction Assisted Liposuction (SAL) and Ultra-sound Assisted Lipoaspiration (UAL) on yield, viability, surface markers and trilineage differentiation potential of isolated SVF from both these samples. Subcutaneous fat tissue was collected by UAL and SAL from the same patient (n=8). Stromal Vascular fraction was isolated by enzymatic digestion and the cell yield and viability were compared. Further, the surface markers from both UAL and SAL isolated SVF was assessed. The isolated SVF was used to isolate adipose-derived stem cells (ADSC's) and the surface markers and trilineage differentiation potential were compared. Statistical analysis: All statistical analysis and graph generation were performed using GraphPad Prism version 9.1.1. Results: The results indicate no significant difference in cell, viability and surface markers of SVF isolated from UAL and SAL. Further, we demonstrate that ADSC's isolated from the SVF of both UAL and SAL are capable of trilineage differentiation. There is no statistically significant difference in the yield and viability of SVF isolated from both UAL and SAL techniques. Since UAL can be used for larger volumes of lipoaspiration, we suggest that UAL would be a suitable method for large volume aspirations that do not affect cell yield and viability. Further expansion of these cells demonstrates that they are capable of trilineage differentiation, indicating their possible use in regenerative therapies.